How tough is it to repeatedly hit the ball in golf? - Shan, G. B.; Zhang, X. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Golf is an increasingly popular sport, whose most challenging skill is the driver swing. There have been a large number of studies characterizing golf swings, yielding insightful instructions on how to successfully structure the swing. Achieving a sub 18 handicap is no longer the primary concern for golfers. Instead, players are now most troubled by a lack of consistency during swing execution. The goal of this study is to determine how to consistently execute repeated quality golf swings. By characterizing both successful and failed swings of 22 experienced golfers, we aim to identify swing parameters that are most sensitive and/or prone to motor control variations. We specifically report on five distinct problem areas, as well as provide suggestions for how to address these problems.